2015
DOI: 10.1182/blood-2015-05-645986
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transfusion with granulocytes from G-CSF/dexamethasone–treated donors in neutropenic patients with infection

Abstract: Key Points Overall, no benefit of granulocyte transfusion therapy was observed, but the power of the study was reduced due to low accrual. Post hoc secondary analysis suggested that patients receiving higher doses tended to have better outcomes than those receiving lower ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
217
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(232 citation statements)
references
References 46 publications
7
217
2
6
Order By: Relevance
“…A recent publication by Teofil et al [24] suggests that patients surviving infections received standard doses (1.5-3.0 × 10e8 cell/kg) with a dose-related effect confirmed in bacterial infections. In the post hoc secondary analysis of the RING study, Price et al [25] found that patients who received an average dose per transfusion of ≥ 0.6 × 10 9 granulocytes per kilogram tended to have better outcomes than those receiving a lower dose. Both studies were performed in patients with existing infections unlike our study where the primary objective was to define the feasibility of providing prophylactic granulocyte transfusion during the induction phase of treatment for AML until sustained ANC recovery, initiation of new therapy, or completion of 6 weeks on study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent publication by Teofil et al [24] suggests that patients surviving infections received standard doses (1.5-3.0 × 10e8 cell/kg) with a dose-related effect confirmed in bacterial infections. In the post hoc secondary analysis of the RING study, Price et al [25] found that patients who received an average dose per transfusion of ≥ 0.6 × 10 9 granulocytes per kilogram tended to have better outcomes than those receiving a lower dose. Both studies were performed in patients with existing infections unlike our study where the primary objective was to define the feasibility of providing prophylactic granulocyte transfusion during the induction phase of treatment for AML until sustained ANC recovery, initiation of new therapy, or completion of 6 weeks on study.…”
Section: Discussionmentioning
confidence: 99%
“…An important alternative to donorcollected GTs are thus ex vivo expanded neutrophils as a manufactured product, produced from multiple donors and cryopreserved to provide an "off the shelf " myeloid progenitor product, to treat patients with prolonged neutropenia with pooled transfusions of standard quality. In these products, GCSF-mobilized peripheral or cord blood from donors is enriched for CD34+ cells and cultured in the presence of hematopoietic cytokines and/or activation of endogenous Notch signaling, leading to an expanded myeloid progenitor cell population with very low or undetectable B-and T-cell lymphoid populations [24][25][26]. Thus these products can transiently give rise to granulocytes and macrophages, and also retain erythroid and platelet-producing potential, however lack the ability to permanently engraft or produce lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte transfusions augment the numbers of circulating neutrophils to support the patient´s immune system during neutropenia and suffering from IFIs. Neutrophil transfusions from healthy donors were shown to be safe in a phase I/II clinical trial for treatment of infections in HSCT patients [33]. Patients who received >0.6 × 10 9 granulocytes/kg per transfusion tended to have a better outcome when compared to a lower dose [33].…”
Section: Pmn Activation Via Il-15 Il-15 Another Keymentioning
confidence: 99%
“…Neutrophil transfusions from healthy donors were shown to be safe in a phase I/II clinical trial for treatment of infections in HSCT patients [33]. Patients who received >0.6 × 10 9 granulocytes/kg per transfusion tended to have a better outcome when compared to a lower dose [33]. Further, granulocyte transfusion was demonstrated to increase survival rates in cancer patients with candidemia, to show good clinical efficacy in various case reports of patients with IA and mucormycosis and to prevent recurrence of fungal infections [22,32,33].…”
Section: Pmn Activation Via Il-15 Il-15 Another Keymentioning
confidence: 99%
“…1 F unctioning granulocytes are a vital component of the defense system against bacterial and fungal infections in humans. For patients undergoing stem cell transplantation or induction for acute leukemia, modern intensive chemotherapy often results in prolonged periods of neutropenia, a major risk factor for severe bacterial and fungal infections.…”
mentioning
confidence: 99%